Metals and the conformation of fibrin - Naidoo, Dhesigen P (Division of Chemical Pathology, 2017)
The carboxy terminal of the γ-chain of human fibrinogen contains at least three biologically. important functional domains: (i) the fibrinogen γ-chain polymerisation centre, (ii) the platelet receptor domain and (iii) the site for staphyloccocal clumping. The nature of the site specificity of these interactions necessitates the existence of a preferred conformation for this region, the nature of which has yet to be clearly established. A novel zinc metalloproteinase isolated from puff adder venom (PAV protease) capable of specifically cleaving the di-γ-chain of transglutaminase (Factor XIIIa) catalysed crosslinked plasmin derived D-dimer into apparently symmetrical monomers has been described. The activity is fibrin specific and displays an unusual site specificity for the γ-carboxy terminal domains within the crosslink region. The activity was reported to be potentiated by zinc. The effect of zinc on the digestion of D-dimer by PAV protease was evaluated by SDS-PAGE and by a fluorimetric technique utilising a fluorescent dansylcadaverine conjugate of the substrate (f-D-dimer). A differential zinc binding study determined that the potentiation of activity by zinc was due to a zinc-substrate rather than a zinc-enzyme interaction. The binding constant for zinc to D-dimer was determined by Scatchard analysis of zinc titration data. The interaction of zinc and f-D-dimer was confirmed by fluorescence anisotropy determinations. The nature of the coordination capsule around the metal cation was determined by examining a cobalt-fibrin-D-dimer complex and characterising the difference visible absorption spectrum thereof. The donor ligands from the D-dimer fragment for the metal ion were determined as histidines by examining zinc(II) and cobalt(II) binding to diethylpyrocarbonate modified fibrin-D-dimer and hydroxylamine treated DEPC-fibrin-D-dimer. Through this study it has been established that the PAV protease cleavage of the di-γ-chain of the plasmin derived D-dimer fragment is potentiated by zinc(II) ions through the formation of a novel zinc determined conformation of fibrin-D-dimer. This presents the possibility of a fibrinspecific neo-epitope being manifested in the presence of zinc ions that could provide a means to determine fibrin degradation products more specifically. A model for the neo-epitope has been proposed.